Core@shell Ti3C2Tx@Ni particles with enhanced microwave absorption properties and prolonged stability. (August 2023) - Xu, Weimin; Li, Shibo; Zhang, Weiwei; Hu, Shujun; Yu, Wenbo; Zhou, Yang
Highlights: Core@shell structured Ti3 C2 Tx @Ni particles were prepared by electroless plating. Thin-shelled Ti3 C2 Tx @Ni exhibited enhanced microwave absorption properties. A reflection loss of −48.36 dB was achieved in the thin-shelled Ti3 C2 Tx @Ni. The Ti3 C2 Tx @Ni particles are stable to 1 year, longer than 12 weeks for Ti3 C2 Tx . The Ni shell prevents Ti3 C2 Tx nanosheets from oxidative degradation. Abstract: 2D Ti3 C2 Tx MXene with a multi-layered structure and surface functional groups exhibits an ability to attenuate electromagnetic energy through the dielectric loss mechanism. However, the absence of magnetic properties causes its unmatched impedance and poor MA performance. In addition, as exposed to air, oxidization of Ti3 C2 Tx generally starts from its nanosheet edges and gradually expands to the inside, causing severe oxidative degradation within days and thus restricting its industrial applications. Here, core@shell structured Ti3 C2 Tx @Ni particles were prepared by electroless plating. The plated thinner Ni(P) shell endows the modified Ti3 C2 Tx particles with good impedance matching with microwaves. A minimum reflection loss (RLmin ) value of -48.34 dB was achieved in the Ti3 C2 Tx @Ni particles, better than the RLmin of ∼ -11 dB for the pristine Ti3 C2 Tx . The core@shell Ti3 C2 Tx @Ni particles are particularly attractive in its storage stability. As compared with the fast and oxidation of Ti3 C2 Tx within 12 weeks, the as-prepared Ti3 C2 Tx @Ni particles are stable up to a year in air because the Ni shell prevents Ti3 C2 Tx nanosheets from oxidative degradation. Graphical abstract: Image, graphical abstract